2018
DOI: 10.1186/s13256-018-1910-x
|View full text |Cite
|
Sign up to set email alerts
|

Perindopril-induced angioedema of the lips and tongue: a case report

Abstract: BackgroundAce inhibitor-induced angioedema, characterized by sudden-onset swelling of the mucous membrane, skin, or both, is a rare occurrence in the Kingdom of Saudi Arabia. Because of its safety and efficacy, perindopril is a commonly prescribed angiotensin-converting enzyme inhibitor. Here we describe the clinical manifestations, management, and outcome of perindopril-induced angioedema of the lips and tongue in a 65-year-old Saudi man.Case presentationA 65-year-old Saudi Arab man presented to an emergency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
7
0
3
Order By: Relevance
“…Estos autores concuerdan que la hidroclorotiazida es un fármaco foto sensibilizante y es importante comunicar el riesgo de este medicamento a los pacientes Kostis et al, (2018) en su investigación relacionado al angioedema inducido por los IECA menciona que esta reacción se produce debido a que los IECA actúan en la inhibición de la degradación de bradiquinina dando como resultado la extravasación de plasma en el tejido submucoso lo cual conduce a angioedema. En un reporte de caso realizado por Alharbi et al, (2018) se relaciona a perindopril perteneciente a los IECA como responsable de angioedema de labios y lengua en un paciente de 65 años. Esta es una afección potencialmente letal, por lo tanto, es necesaria una detección temprana para una intervención terapéutica adecuada.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Estos autores concuerdan que la hidroclorotiazida es un fármaco foto sensibilizante y es importante comunicar el riesgo de este medicamento a los pacientes Kostis et al, (2018) en su investigación relacionado al angioedema inducido por los IECA menciona que esta reacción se produce debido a que los IECA actúan en la inhibición de la degradación de bradiquinina dando como resultado la extravasación de plasma en el tejido submucoso lo cual conduce a angioedema. En un reporte de caso realizado por Alharbi et al, (2018) se relaciona a perindopril perteneciente a los IECA como responsable de angioedema de labios y lengua en un paciente de 65 años. Esta es una afección potencialmente letal, por lo tanto, es necesaria una detección temprana para una intervención terapéutica adecuada.…”
Section: Discussionunclassified
“…El edema es causado por hiper permeabilidad de las vénulas poscapilares debido a agentes vasoactivos (Bezalel et al, 2015). Puede ser potencialmente mortal, si se involucra la mucosa oral, labios, lengua y el tracto respiratorio superior, la hinchazón puede durar de unas pocas horas hasta las 72 horas Se ha observado angioedema inducido por los IECA, también se ha reportado a los bloqueadores de los receptores de la angiotensina II y bloqueadores de los canales de calcio pueden presentar este efecto adverso en menor proporción (Alharbi et al, 2018;Southerland et al, 2016;Weinstock & Johnson, 2016).…”
Section: Angioedemaunclassified
See 1 more Smart Citation
“…Perindopril is one of the ACE inhibitors that is often associated with angioedema of the lips and tongue. The underlying mechanism for ACE inhibitor‐induced angioedema is the enzymatic inhibition of bradykinin degradation (Alharbi et al, 2018 ). Early recognition of drug‐induced tongue oedema is important as it can be a life‐threatening condition.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported cases of drug‐induced tongue disorders (Alharbi et al, 2018 ; Balaji et al, 2014 ; Braggio et al, 2018 ; Brown, 1949 ; Gurvits & Tan, 2014 ; Healy et al, 2004 ; Hubiche et al, 2013 ; Kalogirou et al, 2017 ), but a comprehensive overview of drugs associated with tongue disorders as an adverse effect is not available. Such an overview will support oral healthcare providers in the recognition, diagnosis and eventual treatment of drug‐induced tongue disorders.…”
Section: Introductionmentioning
confidence: 99%